2020
DOI: 10.1002/jsfa.10781
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the volatile profiles of 22 traditional and newly bred maize varieties and their porridges by PTR‐QiTOF‐MS and HS‐SPME GC–MS

Abstract: BACKGROUND Low adoption of maize varieties bred to address the nutritional needs of the growing African population limits their impact. Aroma is essential in consumer preference, but has hitherto hardly been studied. We analysed the volatile organic compounds of flours and porridges of 22 maize varieties belonging to four nutritionally distinct groups, namely provitamin A maize, quality protein maize, yellow and white maize. RESULTS Proton‐transfer‐reaction quadrupole ion time‐of‐flight mass spectrometry (PTR‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…GC-MS is the conventional method for analyzing volatiles in food matrices due to reliable identification and quantification of compounds (Ekpa;Fogliano & Linnemann, 2020), while the complementation with data from the Linear Retention Index (LRI) makes the identification process even more reliable (Rigano et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…GC-MS is the conventional method for analyzing volatiles in food matrices due to reliable identification and quantification of compounds (Ekpa;Fogliano & Linnemann, 2020), while the complementation with data from the Linear Retention Index (LRI) makes the identification process even more reliable (Rigano et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…were the ones that registered the lowest peaks of the volatile compound limonene (LRI of 1207 cps), however, they presented the same odor descriptors (citrus, mint) as the other microalgae analyzed. The aroma of the volatile compound limonene can be classified in addition to citrus and mint, as fruity and floral, and can contribute positively to the aroma of microalgal biomass (Zuo, 2019), even if they have relatively low threshold values (Ekpa;Fogliano;Linnemann, 2020). Caetano et al (2019) and Nass et al (2019), reported that in the microalgae Chlorella vulgaris and Phormidium autumnale, the aroma of limonene was identified as lemon, citrus and orange, since the LRI was 1182 cps, lower than that presented in this study.…”
Section: Resultsmentioning
confidence: 99%
“…Flavor compounds of the samples were measured using GC-MS (PerkinElmer Clarus 500, Norwalk, USA) according to the method described by Ekpa et al (2020) . Briefly, potato flour of 1.5 g was weighed into a 10 mL glass vial and incubated at 40 °C for 15 min.…”
Section: Methodsmentioning
confidence: 99%
“…(E,E)-2,4-Nonadienal was mainly present in Qingzhou, Jinan, and Yishui pancakes, which may originate from oxidative degradation of methyl and ethyl esters of linoleic acid in foxtail millet flour [29] . Hexanal was mainly present in Shenxian and Gaomi pancakes, which were supposed to originate as a reaction product from the oxidation of fatty acid components in yellow maize flour [30] . The nonanal contents in the Linqu pancake were higher than the other samples, which could be related to the degradation of unsaturated fatty acids in soybean flour [31] .…”
Section: Composition Of Aroma Compounds and Key Odorants In Chinese P...mentioning
confidence: 99%